Perilaku Belajar Efektif Terhadap Kemampuan Kognitif Psikomotorik Siswa Dalam Pembelajaran Matematika - Sriyana Sriyana; Widodo Winarso (IndoMath: Indonesia Mathematics Education, 2018)
The research was conducted to learn about the effect of effective learning behavior on students' cognitive-psychomotor skills in class IX mathematics learning at MTs Ash-Shiddiqiyyah Sumber Cirebon. This method of research is quantitative research. The population of this research is composed of all students of class IX MTs Ash-Shiddiqiyyah, The sample of this research is class IX B with a total of 24 students taken from Cluster Random Sampling. The data collection techniques used are 2, ie questionnaires for effective behavioral data and test data for the cognitive-psychomotor skills of students. The technique of data analysis for hypothesis testing is a simple regression analysis technique. The result of this research shows that the result of t-count = 7.522 is greater than t-table = 0.404 so it means that there is an influence between an effective learning behavior towards the ability cognitive-psychomotor of the student in mathematics